Implementation of Activity Based Costing Method in the Yellow Noodle Industry - Afriany, Afriany; Pitoyo, Rubianto (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This study aims to determine the application of the activity based costing method on yellow noodle industry. The activity based costing method is aimed at presenting accurate of cost of products for management purposes, by carefully measuring the consumption of resources in every activity used to obtain maximum profit. This study uses a qualitative model with an evaluation approach, where the interactive model used is three procedures; data reduction, data presentation, and drawing conclusions or verification. Findings, in this study there are 2 inefficient production process activities, namely the activity of the yellow noodle drying process where the allocation of labor costs uses fixed costs and the process of weighing the yellow noodles which uses the same labors as the cost per unit is different. Based on the application of the activity based costing method, the two inefficient activities are converted into variable costs per unit and allocated in the parent process activity. The impact of allocation changes is an increase in profit per unit, from Rp. 6,475 per pack of yellow noodles to Rp. 7,167 per pack of yellow noodles.